Pemanfaatan Tumbuhan Obat oleh Masyarakat Sekitar Taman Wisata Alam (TWA) Bukit Kelam, Kabupaten Sintang, Kalimantan Barat (The Utilization of Medicinal Plants by Communities around Bukit Kelam Nature Park, Sintang Regency, West Kalimantan) - Yusro, Fathul; Pranaka, Resky Nanda; Budiastutik, Indah; Mariani, Yeni (Department of Forestry, Faculty of Agriculture, University of Lampung, 2020)
Bukit Kelam Nature Park has a high diversity of flora, including medicinal plants. This study aimed to analyze the medicinal plants in Bukit Kelam Nature Park with high use value (UV), agreement of community's (informant consensus factor/ICF) in utilizing plant species for specific usage categories, and preferred medicinal plants for the treatment of particular usage (fidelity level/FL). Data was collected through field surveys and interview with respondents in Kebong, Merpak, and Kelam Sejahtera villages. Purposive sampling was used to determine the number of the respondent, and the number of respondents was 30% of the total number of the households (351 respondents). The results showed that 84.61% of respondents used 198 species of medicinal plants. Eleven species had high UV, and 5 of them were Curcuma longa (0.3761), Piper betle (0.2422), Psidium guajava (0.2308), Syzygium polyantum (0.1510), and Eleutherine bulbosa (0.1481). The high ICF for the usage category were for body odor, bad breath, diet, acne, nosebleeds, coughs, diarrhea, hypertension, and internal injuries. Fifty-eight species had high FL values (100%), and 5 of them were Erythrina subumbrans (fever), Heliconia rostrata (diabetes), Hippobroma longiflora (dysentery), Cassia alata (skin infection), and Baccaurea motleyana (sore eyes). Keywords: Bukit Kelam, conservation, local wisdom, traditional medicine